Determinasi Manajemen Laba Pada Perusahaan Yang Terkategori Daftar Efek Syariah - Muhammad Ash-shiddiqy (Jurnal Akuntansi dan Keuangan Islam, 2019)
This study aimed to investigate the effect of IFRS convergence and Gorporate Governance on Earnings Management in companies listed on the Daftar Efek Syariah, in addition, this study also intends to prove the alleged differences in the level of earnings management before and after Convergence IFRS enacted. Variables used in this research are the convergence of IFRS, independent commissioners, audit committee, managerial ownership and institutional ownership with a sample of 17 companies. The Test was using regression methods and paired sample t test. Based on the output of the regression, the results of the analysis found a significant relationship between the variables IFRS convergence and institutional ownership to earnings management, while variable independent commissioners, audit committee, and managerial ownership have no effect. The second test, using paired sample t test found no difference in the average level of earnings management before and after IFRS convergence.